Acupuncture Treatment of Chest Bi Syndrome - 胡金生 王新中（译） (Journal of traditional Chinese medicine, 2008)
A male, a retired officer of 61 years old, paid his first visit on May 12, 2006. The patient stated that 2 weeks before he suddenly got paroxysmal precordial choking pain, with irregular attacks. Each attack would last several seconds to several minutes. The attack was accompanied with heavy oppressed sensation in the precordial region, palpitation, lassitude, and in severe cases, sweating,